Editorial - Hyun Jun Park; Nic Clear (Architecture Image Studies Scientific Journal)
This is the third special issue that Clear+Park (C+P) have edited for AIS, and working with them has once again been a hugely enjoyable experience. In all our collaborations, we have enjoyed enormous freedom in the type of projects that can be included, especially the license to mix practice-based projects and speculative approaches alongside more traditional academic text-led pieces.